(untitled) (Research, Society and Development, 2022)
Soybean is one of the most important crops for the Brazilian economy, as it is one of the most consumed oilseeds in the world. It is currently one of the fastest growing crops in Brazil, with an increase in the area produced and productivity. However, for this to occur, it is necessary for producers to acquire seeds of high physiological quality, free of pathogens, and with high germination and vigor, ensuring adequate stands in the field. Diseases are one of the main aggravating factors in the decrease in the quality of soybean seed lots. Thus, this work aims to collect soybean seeds cultivar BRASMAX BÔNUS IPRO - 8579 RSF to determine the sanitary quality of different batches of seeds, in addition to collecting information on the actions of producers in Marcelândia-MT. To carry out the sanitary analysis, the blotter test method was used, using filter paper in transparent acrylic boxes (gerbox). Sample 3498 was the one with the highest number of diseases among the lots analyzed with the presence of Penicillium sp., Cercospora kikuchii, Fusarium spp., Bacteria and Colletotrichum truncatum. Sanity analyzes showed that all seed lots had some type of pathogen.